2018
DOI: 10.1038/s41426-018-0165-3
|View full text |Cite|
|
Sign up to set email alerts
|

Small molecules targeting coxsackievirus A16 capsid inactivate viral particles and prevent viral binding

Abstract: Coxsackievirus A16 (CVA16) is an etiologic agent of hand, foot, and mouth disease (HFMD) that affects young children, and although typically self-limited, severe complications, and fatal cases have been reported. Due to the lack of specific medication and vaccines against CVA16, there is currently a need to develop effective antivirals to better control CVA16 infections in epidemic areas. In this study, we identified the tannins chebulagic acid (CHLA) and punicalagin (PUG) as small molecules that can efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Identifying antiviral agents that restrict EBOV entry into host cells and prevent establish-ment or limit propagation of its infection are advantageous as they could serve not only as therapeutic drugs, but also for prophylaxis purposes (pre-or post-exposure) which is key in reducing viral transmission and providing protection for high-risk healthcare workers [37]. Indeed, entry inhibitors have emerged as an important class of antiviral agents for the prevention/treatment of various viral infections and have been explored widely, including against HIV-1 [38][39][40][41], herpes simplex virus [28,42], avian influenza [43,44], dengue virus [45,46], hepatitis C virus [23,26,[47][48][49], measles virus [50,51], and enteroviruses [52,53]. These developments prove the utility and significance of entry inhibitors as a vital class of antiviral agents.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying antiviral agents that restrict EBOV entry into host cells and prevent establish-ment or limit propagation of its infection are advantageous as they could serve not only as therapeutic drugs, but also for prophylaxis purposes (pre-or post-exposure) which is key in reducing viral transmission and providing protection for high-risk healthcare workers [37]. Indeed, entry inhibitors have emerged as an important class of antiviral agents for the prevention/treatment of various viral infections and have been explored widely, including against HIV-1 [38][39][40][41], herpes simplex virus [28,42], avian influenza [43,44], dengue virus [45,46], hepatitis C virus [23,26,[47][48][49], measles virus [50,51], and enteroviruses [52,53]. These developments prove the utility and significance of entry inhibitors as a vital class of antiviral agents.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it inhibits the entry of herpes simplex virus 1 and other viruses by antagonizing the interactions of viral glycoprotein and cell-surface glycosaminoglycans [47][48][49][50]. It can also inhibit the viral NS3-4A protease of hepatitis C at low micromolar concentrations [33] and may also target the capsid protein of coxsackievirus A16 [51]. Notably, 1 mg/kg chebulagic acid also reduced mouse mortality following a lethal dose of human enterovirus 71, indicating that antiviral activity extends to in vivo models [52].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that this phenomenon is affected by the metabolic profile of the extracts. For example, Lin et al [20] found that polyphenols, such as tannins are effective against coxsackieviruses. None of the concentrations tested were cytotoxic (Figure 3C), which was evaluated using CPE Inhibition assay.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Tannins and other polyphenols have indeed been previously identified with antiviral activities. For example, Lin et al [20] found that tannins chebulagic acid and punicalagin significantly reduced the coxsackievirus infectivity by both inactivating cell-free viral particles and inhibiting viral binding. In another study by Du et al [33], resveratrolloaded nanoparticles were successful in inhibiting enterovirus replication and protecting rhabdosarcoma cells in vitro.…”
Section: Metabolite Profilesmentioning
confidence: 99%